Making Sense of Chondrite Meteorites - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2022)
I describe the simplification of multitudes of complex data on hundreds of chondrite meteorites to obtain a fundamental relationship that underlies processes during solar system formation. From the relationship derived, generally, it can be concluded that only three processes, operant during solar system formation, are responsible for the diversity of matter in the solar system, as well as for planetary compositions , internal-structures, dynamics and magnetics: (1) Condensation at very high-pressures; (2) Condensation at very low-pressures; and (3) Scouring of the inner solar system by the T-Tauri eruptions during thermonuclear ignition of the sun.